ANALYSIS OF AIR FLOW THROUGH THE ENGINE INTAKE AND EXHAUST DUCTS - Czyż, Zbigniew (Journal of Technology and Exploitation in Mechanical Engineering _ARCHIVE ISSUES, 2019)
The paper presents numerical analysis of charge exchange in an opposed-piston two-stroke engine. The research engine is a newly designed internal diesel engine. This unit is composed of three cylinders in which operate three pairs of opposed-pistons. The numerical investigations were carried out using ANSYS FLUENT solver. The geometrical model includes an intake manifold, a cylinder and an outlet manifold. The calculations specified a swirl coefficient obtained under steady conditions for fully open intake and exhaust ports as well as the CA value of 280° for all cylinders. In addition, mass flow rates were identified separately in all of the intake and exhaust ports to achieve the best possible uniformity of flow in particular cylinders.